Which is a better treatment for carotid artery stenosis: stenting or endarterectomy? - BİLGİN, MEHMET; BURGAZLI, K. M.; Bilgin, MEHMET; KAVUKCU, E.; MERICLILER, M.; BOHL, N.; ATMACA, N. (My University, 2013)
Carotid stenosis amenable to surgical or interventional revascularization accounts for 5-12% of all new strokes. Several randomized trials have shown that carotid endarterectomy (CEA) for the treatment of symptomatic and asymptomatic carotid stenosis is superior to medical treatment. Application of a carotid artery stent (CAS) representing a good alternative for many patients. CAS application has become comparatively safe with the use of embolism-preventive systems developed in recent years. Complication rates reported in some randomized trials and case studies in the literature are similar with CEA. CAS may be recommended as the first choice or alternative treatment for patients with symptomatic stenosis carrying high risks for open surgery. However, more randomized studies are necessary to recommend CAS for patients carrying at low surgical risks or patients with asymptomatic stenosis. This is a systematic review of the literature investigating the effectiveness of the treatment methods for carotid artery stenosis.